A Surgeon's Dilemma - Shuman, Andrew G. (The Hastings Center report, 2016)
A thirty-year-old single mother with recurrent, metastatic, treatment-refractory cancer presents to the emergency room with severe difficulty breathing due to an obstructive tumor in her neck, compounded by progressive disease in her lungs and a new pulmonary embolism. She cannot be safely intubated and would require an emergent awake tracheotomy. Even if the airway can be successfully secured surgically, the likelihood that she will be able to be weaned from mechanical ventilation is very low. The surgeon, a young mother too, appreciates the patient's desire for more time with her toddler. But the surgeon knows the significant risk of surgery, the massive responsibility she would accept in trying to get the patient through it, and the emotional toll of an intraoperative death on surgical staff. And she can imagine the second-guessing that will come during the inevitable morbidity and mortality conference if the patient should die in the perioperative window. Yet the surgeon does not want to take the “easy” way out; after all, critically ill patients undergo aggressive resuscitation all the time. What should she do?